2021
DOI: 10.1007/jhep06(2021)116
|View full text |Cite
|
Sign up to set email alerts
|

On ambiguities and divergences in perturbative renormalization group functions

Abstract: There is an ambiguity in choosing field-strength renormalization factors in the $$ \overline{\mathrm{MS}} $$ MS ¯ scheme starting from the 3-loop order in perturbation theory. More concerning, trivially choosing Hermitian factors has been shown to produce divergent renormalization group functions, which are commonly understood to be finite quantities. We demonstrate that the divergences of the RG functions are such t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…In ref. [42], we found that there always exists a choice of renormalization constants for which β I is identical to B I (meaning that υ = 0). Thus it is perfectly valid to use B I in place of β I for the RG, a choice that also carries the benefits discussed above.…”
Section: Jhep01(2022)051mentioning
confidence: 85%
See 4 more Smart Citations
“…In ref. [42], we found that there always exists a choice of renormalization constants for which β I is identical to B I (meaning that υ = 0). Thus it is perfectly valid to use B I in place of β I for the RG, a choice that also carries the benefits discussed above.…”
Section: Jhep01(2022)051mentioning
confidence: 85%
“…The MS β-functions are generally not unique beyond the second loop order. The flow in the direction of flavor symmetry transformations (the symmetry of the kinetic term of Lagrangian (2.1)) is fixed by the choice of renormalization constants, which are themselves ambiguous [42]. It can even be divergent in the dimensional expansion, although physics is insensitive to any such flavor rotations along the flow due to the symmetry of the action under combined field and coupling transformations.…”
Section: Flavor-improved β-Functionmentioning
confidence: 99%
See 3 more Smart Citations